The association between dental health and nutritional status in chronic obstructive pulmonary disease. (November 2017) - Terashima, Takeshi; Chubachi, Shotaro; Matsuzaki, Tatsu; Nakajima, Takahiro; Satoh, Minako; Iwami, Eri; Yoshida, Kyouko; Katakura, Akira; Betsuyaku, Tomoko
Chronic obstructive pulmonary disease (COPD) and periodontitis are chronic inflammatory systemic diseases with common risk factors (smoking and aging). In COPD, poor periodontal health could result in inadequate nutrition, potentially causing loss of muscle volume. The purpose of this case-control study was to examine our hypothesis that COPD patients have poorer periodontal health and poorer nutritional status than non-COPD patients. Periodontal status was assessed using bleeding on probing (BOP), pocket depth (PD), and plaque–control ratio (PCR). Nutritional status was assessed using body mass index, lean body mass, and serum albumin levels. The COPD group ( n = 60) had fewer remaining teeth, greater BOP, greater PD, and lower serum albumin levels compared with smokers without COPD ( n = 41) and nonsmokers ( n = 35; p < 0.001). COPD was an independent risk factor for poor periodontal health, demonstrated by fewer remaining teeth (relative risk (RR), 5.48; p = 0.0024), BOP (RR, 12.8; p = 0.0009), and having >30% of remaining teeth with a PD ≥ 4 mm (RR, 4.82; p = 0.011). A significant negative correlation existed between the number of teeth with a PD ≥ 4 mm and serum albumin level ( r 2 = 0.127; p = 0.013). We demonstrated that poor periodontal health was associated with hypoalbuminemia, suggesting poor nutritional status and inflammation in COPD.